RESPON MASYARAKAT TERHADAP PERAN POLITIK KYAI - Puji Qomariyah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This research aims to be describe about position, existence and kyai’s inflences in political-community behavior. In fact, there are few research that design for grass root and sometimes elitecentrist more dominant; from this angle/view: research tried to be promote phenomenon in Rembang, a residence at CentralJava province that have base political development in the name of Islam. Usage survey method and technique sampling with Moment product correlation, Partial correlation and Regression correlation to examine hypothesis; research (observation and tracking) found attractive cases: materialistic kyais made fadeaway their charisma; moreover if kyais take hold in official government, as stake-holder in political parties; fially people’s trust in kyai decrease. Decline people’s trust in their kyais, cause bring about their affiiation in certain political-parties choices is not signifiant. They courageous be different with kyai’s political-parties choice. Unwilling visit kyai or passed away/ disappear “sowan” tradition, take kyai’s hand to kiss in order to get kyai’s blessed with reluctantly; in fact people consider that existence and kyai’s inflences is not important in their life. In political behavior, kyais’ attitude is not inflence in their behavior, included their specifid-chooses political parties that similar with their kyai’s. Commonly; people conclude, there are no benefi although choices the same parties (kyai’s politicalparties choice. red); and no signifiant alteration in people life.